Carpal tunnel syndrome caused by tophi deposited under the epineurium of the median nerve: A case report - Zhang, Wenzhong; Feng, Qingbo; Gu, Jiaxiang; Liu, Hongjun (Frontiers in Surgery, 2023)
Introduction: Carpal tunnel syndrome (CTS), the most common type of peripheral neuropathy, is caused by compression of the median nerve at the wrist. Tophi deposited under the epineurium of median nerve compress the median nerve, leading to CTS is very rare. Case Presentation: We report a 64-year-old man with a history of tophaceous gout who presented with typical CTS symptoms admitted to our hospital. During routine physical examination, swelling was present over the right volar aspect of the carpal region, and he was unable to flex because of subcutaneous rigidity. Positive Tinel’s sign and Phalen’s maneuver were present. Electrophysiological studies confirmed the diagnosis of CTS. Afterward, carpal tunnel release and excision of gouty tophus of the right wrist was done at which time the serum uric acid level was within normal range (5.7 mg/dl). During the operation, tophi deposited under the epineurium of median nerve was found and the tophi was completely removed. Operative findings confirmed the diagnosis of CTS due to gout. The patient recovered uneventfully without sighs of recurrence of gout and CTS symptoms during a 1-year follow-up period. Conclusion: Gouty tophi are an uncommon cause of CTS and gouty tophi should be considered as a possible cause of CTS if there is evidence of extrinsic compression of median nerve or symptoms originating from carpal tunnel.